Characterization and phylogenetic relationship of the complete mitochondrial genome of Black-cheeked Lovebird, Agapornis Nigrigenis - Chen, Yun-Xia (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial genome of Agapornis nigrigenis was obtained using Sanger sequencing. The mitochondrial genome from A. nigrigenis is 16,718 bp in length. Its genome with an overall GC content of 48.86%, contained 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes, and 1 control region. The phylogenetic position of A. nigrigenis based on the 18 parrots species showed it was sister to the same genus specie Agapornis roseicollis. The results obtained here can contribute to molecular evolution and phylogeny of parrots further.